Indonesian Salafist Interpretation of Anthropomorphism Verses on YouTube - Romadlon, Dzulfikar Akbar; Biyanto, Biyanto (Universitas Darussalam Gontor, 2023)
Salafism and Ash’arism have debated the issue of anthropomorphism verses for a long time. In modern days, both followers spread the debate through social media. This article will discuss Indonesian Salafist’s statement on interpreting anthropomorphism verses on YouTube. We will use Critical Discourse Analysis (CDA) from Fairclough’s perspective to investigate how such discursive practices arise from and are ideologically shaped by power relations and power struggles. We conclude that the Salafists frame Ash’arite as Ahl al-Bid’ah because they distort the meaning of anthropomorphic verses. Salafi groups try to present rational arguments for their beliefs to convey to the public that what they believe is rational. As part of the global Salafist movement, the Indonesian Salafists spread their thoughts through various channels on YouTube and received a negative response from Nahdatul Ulama, an Ash’arite adherent, in the comments column. From a power relationship perspective, we can read that the Salafist group is trying to spread its theology to society. Ash’arism, as the majority sect in Indonesia, is trying to defend itself from the spread of Salafism.